2012
DOI: 10.3415/vcot-11-01-0012
|View full text |Cite
|
Sign up to set email alerts
|

Canine total knee replacement performed due to osteoarthritis subsequent to distal femur fracture osteosynthesis

Abstract: A 27-kg German Shorthaired Pointer was referred for evaluation due to the complaint of left pelvic limb lameness and signs of pain in the left stifle joint. Radiographs revealed signs of a healed supracondylar femoral fracture that had been previously repaired at another hospital with an intramedullary pin and two cross pins. In addition, there were signs of severe osteoarthritis (OA). The OA had been managed medically with administration of carprofen and nutraceuticals for nine months without any improvement.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The following three parts were then included in every round of data collection: (i) Of a total of 19 pain related descriptive scale (0–4) questions on attitude, behaviour, and locomotion, 11 questions formed the owner-assessed HCPI, as described previously [44-47]. (This index now has a new English translation that is closer to the Finnish original; the HCPI-E2, but the validated original remains the same [47,48]). (ii) Two 10-cm VAS: one for lameness and the other for quality of life (QOL).…”
Section: Methodsmentioning
confidence: 99%
“…The following three parts were then included in every round of data collection: (i) Of a total of 19 pain related descriptive scale (0–4) questions on attitude, behaviour, and locomotion, 11 questions formed the owner-assessed HCPI, as described previously [44-47]. (This index now has a new English translation that is closer to the Finnish original; the HCPI-E2, but the validated original remains the same [47,48]). (ii) Two 10-cm VAS: one for lameness and the other for quality of life (QOL).…”
Section: Methodsmentioning
confidence: 99%
“…Kinetic gait analysis has become an accepted technique for accurate and objective evaluation of limb function in humans and animals [ 17 , 18 ]; for that reason, force platform gait analysis can be used as a tool to determine pain, disease, and healing of different units of the locomotor system [ 19 21 ]. In the same manner, this device is consistently used as an accurate, objective method to document the efficacy of different medical treatments of OA in dogs [ 22 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary indication for total knee replacement (TKR) in dogs, just as in man, is end-stage osteoarthritis, 1,2 and the success of canine TKR with both commercial and custom-made implants has been previously demonstrated. [1][2][3][4][5] Feline TKR was first described in a trial in which researchers investigating human metacarpophalangeal joint prostheses used cats as an experimental model. 6 Subsequent researchers reported that a silicon human finger joint prosthesis could be used for TKR in cats, but studies were limited by a small sample size and a short observation period of only 3 months.…”
Section: Introductionmentioning
confidence: 99%